TUSC2P suppresses the tumor function of esophageal squamous cell carcinoma by regulating TUSC2 expression and correlates with disease prognosis - Fengqiong Liu; Ruijie Gong; Baochang He; Fa Chen; Zhijian Hu (BMC Cancer, 2018)
Abstract Background Pseudogenes are RNA transcripts with high homology with its parent protein-coding genes. Although pseudogenes lost the ability to produce protein, it still exert import biological function, and play important role in the pathogenesis of a wide varity of tumors; However, the role of pseudogenes in esophageal squamous cell carcinoma (ESCC) is poorly understood. Methods TUSC2P function in ESCC were explored using both in vitro and in vivo experiments cell proliferation, invasion and apoptosis assay was performed to evaluated the effect of TUSC2P on the tumor biology of ESCC. Expression of relative genes was assessed by quantitative real-time PCR (qRT-PCR) and western blotting in EC109 and TE-1 cell, as well as ESCC patients. 3’UTR luciferase assay was used to confirm the direct binding of miRNAs with TUSC2 and TUSC2P 3’UTR. Relation betweenTUSC2P, TUSC2 and ESCC prognosis was predicted by survival analysis (n = 56). Results Pseudogene TUSC2P was down regulated in ESCC tissues compared with paired normal adjacent tissues, and the expression of TUSC2P was significantly correlated with survivalof ESCC patients. Over expression of TUSC2P in EC109 and TE-1 cells resulted in altered expression of TUSC2, thus inhibited proliferation, invasion and promoted apoptosis. Dual luciferase assay demonstrated that TUSC2P 3’UTR decoyed miR-17-5p, miR-520a-3p, miR-608, miR-661 from binding to TUSC2. Conclusions TUSC2P can suppresses the tumor function of esophageal squamous cell carcinoma by regulating TUSC2 expression and may also serve as a prognostic factor for ESCC patients.